2021
DOI: 10.1186/s13018-021-02564-6
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient blood supply of fovea capitis femoris, a risk factor of femoral head osteonecrosis

Abstract: Background A defective nutrient foramen in the fovea capitis femoris was hypothesized to reflect the blood circulation pattern of the femoral head, leading to insufficient blood supply and causing osteonecrosis of the femoral head. Methods Normal and necrotic femoral head specimens were collected. The necrotic femoral head group was divided into a non-traumatic and traumatic subgroup. 3D scanning was applied to read the number, the diameter, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…However, our study found no difference in the number of foramina between the sexes. It was found that the risk of avascular necrosis decreased as the number of foramina increased in a study by gender independently [10]. Another study found that male are more likely than female to develop avascular necrosis [33].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, our study found no difference in the number of foramina between the sexes. It was found that the risk of avascular necrosis decreased as the number of foramina increased in a study by gender independently [10]. Another study found that male are more likely than female to develop avascular necrosis [33].…”
Section: Discussionmentioning
confidence: 95%
“…In addition, an excess of nutrient foramina reduces the likelihood of developing osteonecrosis [6]. Hip dysplasia and osteoarthrosis have been related to modi cations in the morphometric structure and location of the FCF in the hip joint [10][11][12]. As the femoral head is supplied by vessels that travel through the FCF, the features of the anatomical structures on the head of the femur are considered potential factors in avascular necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…The fracture maps generated in this study could also aid in the evaluation of vascular damage to the femoral head of patients with DFNFs. The absence of nutrient foramina in the fovea capitis femoris has been shown to be associated with a high likelihood of femoral head osteonecrosis ( 25 ). Thus, a residual blood supply around the femoral head and neck junction is crucial for patients with DFNFs, especially when nutrient foramina are absent from the fovea capitis femoris.…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient blood supply to the femoral head has been suggested as a pathogenic mechanism of ONFH ( Zhao K. et al, 2021 ). Several studies have investigated the relationship between polymorphisms in the VEGF gene and the risk of ONFH; however, the results are inconsistent and contradictory.…”
Section: Association Between the Polymorphisms Of Growth Factor-relat...mentioning
confidence: 99%